Without women there is no democracy: indigenous women and prior consultation processes in Peru - De La Cruz Huamán, Rosario Betzabeth (2022)
This article analyzes the participation of indigenous women in Peru, specifically in prior consultation processes. It should be noted that this is a specific right of indigenous peoples recognized in the international and national regulatory framework, whose main purpose is to establish agreements with the State before any measure of a legislative or administrative nature that affects the collective rights of these peoples. Despite this, there are a series of general difficulties in its application and particular difficulties with regard to the participation of indigenous women, who experience multiple inequality gaps that affect their development. Likewise, these barriers constitute a violation of the principle of equality and non-discrimination, as well as obstructing the path of building a State with democratic action that contributes to interculturality and gender equality.